HIV-1 exploits LBPA-dependent intraepithelial trafficking for productive infection of human intestinal mucosa. - Anusca G Rader; Alexandra P M Cloherty; Kharishma S Patel; Dima D A Almandawi; Dasja Pajkrt; Katja C Wolthers; Adithya Sridhar; Sterre van Piggelen; Liselotte E Baaij; Renée R C E Schreurs; Carla M S Ribeiro (PLoS Pathogens)
The gastrointestinal tract is a prominent portal of entry for HIV-1 during sexual or perinatal transmission, as well as a major site of HIV-1 persistence and replication. Elucidation of underlying mechanisms of intestinal HIV-1 infection are thus needed for the advancement of HIV-1 curative therapies. Here, we present a human 2D intestinal immuno-organoid system to model HIV-1 disease that recapitulates tissue compartmentalization and epithelial-immune cellular interactions. Our data demonstrate that apical exposure of intestinal epithelium to HIV-1 results in viral internalization, with subsequent basolateral shedding of replication-competent viruses, in a manner that is impervious to antiretroviral treatment. Incorporation of subepithelial dendritic cells resulted in HIV-1 luminal sampling and amplification of residual viral replication of lab-adapted and transmitted-founder (T/F) HIV-1 variants. Markedly, intraepithelial viral capture ensued an altered distribution of specialized endosomal pathways alongside durable sequestration of infectious HIV-1 within lysobisphosphatidic acid (LPBA)-rich vesicles. Therapeutic neutralization of LBPA-dependent trafficking limited productive HIV-1 infection, and thereby demonstrated the pivotal role of intraepithelial multivesicular endosomes as niches for virulent HIV-1 within the intestinal mucosa. Our study showcases the application of primary human 2D immune-competent organoid cultures in uncovering mechanisms of intestinal HIV-1 disease as well as a platform for preclinical antiviral drug discovery.